The knowledge about HIV/AIDS and antiretroviral treatment of patients receiving antiretroviral therapy - Terblanche, Lauren Muriel (Stellenbosch : Stellenbosch University, 2012)
Thesis (MCur)--Stellenbosch University, 2012.